2021
DOI: 10.5191/jiaee.2021.28301
|View full text |Cite
|
Sign up to set email alerts
|

Model of Success: Extension Services Helping Ugandan Youth Find A Career in Agriculture

Abstract: As the world continues to experience a population boom amidst growing food insecurity concerns, the need for well-trained and competent youth in agriculture-related industries is on the rise in Sub-Saharan African countries, specifically Uganda. With 78 percent of Uganda’s population below the age of thirty, the number of unemployed and unskilled workers presents a challenge to a country that relies heavily on jobs within the agricultural sector to thrive. Due to the increased number of unskilled youths, exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…e concepts related to innovation and their applications in entrepreneurship, leadership, technology, medical care system, and pharmaceutical business will be taught [7]. A mixed method study of American idiopathic medical schools found that the number of entrepreneurial education programs in medical education was small but growing rapidly.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e concepts related to innovation and their applications in entrepreneurship, leadership, technology, medical care system, and pharmaceutical business will be taught [7]. A mixed method study of American idiopathic medical schools found that the number of entrepreneurial education programs in medical education was small but growing rapidly.…”
Section: Literature Reviewmentioning
confidence: 99%